Analysis of explosion images obtained with high-speed camera with image processing and prediction of explosion loads - Onat Alakuş, Dilan; Türkoğlu, İbrahim (Murat Yakar, 2025)
Visual data-based analysis of explosion events is important in areas including security, disaster management and industrial safety. Understanding the distribution of these events not only helps detect them as they happen, but also facilitates informed decision making for mitigation and intervention strategies. Various experimental methods have been used in the literature on this subject and empirical formulas have been produced. These formulas are still used today, but they are based on limited experimental data. Statistical methods measure the distribution of these data, allowing measurements such as frequency and spatial clustering to identify patterns in the analyzes obtained from the experimental data. Visualization tools further explain these findings, helping to understand and support decision. During and after the explosion, various effects arise from the explosion. These effects are effects such as sound, explosion-induced flash of light, blast wave, craters, tremors. Various sensors are used to measure these effects. These sensors can be damaged during explosion or when used for experimental methods and are very costly. The aim of the study is to increase the predictability of security measures and to reduce the need for high-cost devices by using classical image processing methods. Explosion images were obtained using a high-speed camera for this study. The aim of the study is to analyze blast waves, which are the most fundamental and most destructive effect of the explosion event. Explosion waves occur at a speed imperceptible to the human eye and are damped in very short periods of time. These waves were tried to be detected by using a high-speed camera and image processing methods, and it was aimed to obtain information about explosive charges from these waves. As a result of the study, blast waves have been successfully detected and explosive loads have been successfully analyzed using experimental studies in the literature. © Author(s) 2024.
Keywords: Blast loads; Blast waves; Image processing; Prediction